PENGEMBANGAN MODUL AJAR BERORIENTASI ESD PADA MATERI HEMAT ENERGI DI KELAS VI SEKOLAH DASAR - Hikmah, Putri Durrotul; Suratmi, Suratmi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This research aims to evaluate the quality of ESD (Education for Sustainable Development) oriented teaching modules on energy saving material in class VI elementary school which were developed to support the teaching and learning process. The main issue faced is the lack of valid and effective ESD-oriented teaching modules used by teachers. This research offers a solution by developing teaching modules using research and development methods based on 4D models (Define, Design, Develop, Disseminate). Expert first validation showed 96,1% results in the "Very Valid" category, Expert second validation showed 98% results in the "Very Valid" category, Expert third validation showed 98% results in the "Very Valid" category. Apart from that, the response from teaching practitioners (Teacher) to the teaching module showed a score of 92,8% in the "Very Good" category and the students’ response to the learning showed a score of 96,3% in the "Very Good" category. In conclusion, the ESD-oriented teaching module on energy saving material in class VI elementary school is considered very valid and suitable for use in classroom learning activities.